1996
DOI: 10.1046/j.1537-2995.1996.36696269515.x
|View full text |Cite
|
Sign up to set email alerts
|

Third‐generation recombinant immunoblot assay: comparison of reactivities according to hepatitis C virus genotype

Abstract: The current RIBA-3 lacks sensitivity to the NS4 antibody for HCV types 2 and 3. The incorporation of type-specific components to other genotypes for NS4 (and NS3) antigens should be considered by the manufacturers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…c HBsAg was not detected in these children when tested at 8 months of age. genotype 2 [Dow et al, 1996;Zein et al, 1997]. Data from this study suggest that infection with genotype 4 is highly prevalent in Tanzania, as in other African countries [Xu et al, 1994;Smuts and Kannemeyer, 1995;Oni and Harrison, 1996].…”
Section: Discussionmentioning
confidence: 54%
“…c HBsAg was not detected in these children when tested at 8 months of age. genotype 2 [Dow et al, 1996;Zein et al, 1997]. Data from this study suggest that infection with genotype 4 is highly prevalent in Tanzania, as in other African countries [Xu et al, 1994;Smuts and Kannemeyer, 1995;Oni and Harrison, 1996].…”
Section: Discussionmentioning
confidence: 54%
“…The occurrence of HCV RNA detectable in patients with negative anti-HCV can be a consequence of immunossupression with decreased production of antibodies, or the window period of a recent infection (Sharara et al 1996, Lok & Gunaratnam 1997. Another possibility is the absence, in the serology kits used, of an antigenic variant that is present in the geographic area studied (Dow et al 1996). Other studies also detected HCV or HBV nucleic acids in anti-HCV negative or HBsAg-negative/IgM anti-HBc-positive hemodialysis patients, respectively (Carneiro et al 2001, Lewis-Ximenez et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is difficult to identify the most sensitive assay to NS4. A recent report indicated that RIBA-3 lacked sensitivity to the NS4 antibody for HCV types 2 and 3 [9]. Not all the genotypes of the 44 positive samples of our panel were determined.…”
Section: Discussionmentioning
confidence: 93%